Essays in Public Sector Entrepreneurship - Audretsch, David B.; Link, Albert N. (International Studies in Entrepreneurship,, 2016)
This book explores public sector entrepreneurship from an international perspective. It features essays from eminent scholars in the field addressing entrepreneurial public policies from different countries. Public sector entrepreneurship is at the cusp of becoming a watchword in international policy circles. This book is a pioneer volume in this emerging field and provides topics and policies that are broadly applicable across different economies. Public sector entrepreneurship refers to innovative public policy initiatives that generate greater economic prosperity by transforming a status-quo economic environment into one that is more conducive to economic units engaging in creative activities in the face of uncertainty. In today's economy, public sector entrepreneurship affects that transformation primarily by increasing the effectiveness of knowledge networks; that is, by increasing the heterogeneity of experiential ties among economic units and the ability of those same economic units to exploit such diversity. Through policy initiatives that are characterized by public sector entrepreneurship, there will be more development of new technology and hence more innovation throughout the economy.